Totemo Oishi Bakery / Muhamamad Danial Haziq Zairel … [et al.] - Zairel, Muhamamad Danial Haziq; Mohamad Yusof, Muhammad Hasief; Mohamad Roslan, Muhammad Zikrul Hakim; Kamarol Shaharim, Hambali; Razali, Muhammad Hanif Firdaus (2021)
The name for this company is TOTEMO OISHI BAKERY. The corporation is focused sole proprietorship where it consists single owner as general manager and four employees hold important positions and play such major roles in the company. The positions include Administrative Manager, Marketing Manager, Operational Manager and Financial Manager as well. It specifically shows that this organization created a bakery company that distributes bakery products. Referring to the name of this company, TOTEMO OISHI BAKERY has picked cake as its key market product. Cakes are sugar, fat and egg-rich baking products which can be supplemented by a wide range of inclusions like fruits and aromas, like vanilla and chocolate extracts. In addition, the word "TOTEMO OISHI" derives from the phrase "A delicious range of cake" which means that customers who eats Totemo Bakery's cakes can simply enhance their feeling towards the delicious taste of cakes, making them remember the precious moments with loves and satisfy their unlimited wants. TOTEMO OISHI BAKERY is a prosperous company that still has a high degree of demand on the market for baking goods. The customers are therefore undoubtedly residents of Shah Alam, Selangor which is the location of the firm. The business decides to make the items more appealing and interesting through imagination in the form of desserts, mixed color and ingredients. Each of TOTEMO OISHI BAKERY'S cakes products has their own specialties that make them distinctive from other cakes sold on the market. The organization also assumes that products from other rivals will compete with baking products.